Sand as a catalyst for community innovation and sustainable development in Ezakheleni informal settlement, Umlazi, South Africa: A cross-sectional study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background The use of natural resources, such as sand, is traditionally associated with large-scale industries like construction and manufacturing. However, its potential to drive local business innovation and sustainable development remains underexplored, particularly within South Africa’s pursuit of the Sustainable Development Goals (SDGs). This study aimed to investigate how sand-based entrepreneurship can promote community-driven sustainable development and contribute to achieving SDG-aligned outcomes. Methods A mixed-methods approach was adopted. Qualitative data were gathered through in-depth interviews with 45 local entrepreneurs and community leaders across four South African provinces. Quantitative data were obtained by analysing 60 sand-based business ventures, focusing on income generation, employment creation, and contribution to SDG targets. Data were analysed using thematic analysis for qualitative findings and descriptive statistics for quantitative data. Results Quantitative findings showed that 67% of the businesses reported income growth of over 30% within two years of operation, while 58% generated permanent employment for 3 to 7 local workers per venture. Additionally, 72% of the businesses reported alignment with SDG 9 (Industry, Innovation, and Infrastructure), and 64% supported SDG 12 (Responsible Consumption and Production). Qualitative insights revealed that integrating traditional knowledge with eco-friendly innovation enhanced both resilience and market appeal. Community participants reported that such ventures contributed not only to income but also to broader social cohesion and local empowerment. Conclusion When utilized through innovative and sustainable approaches, sand-based community enterprises can significantly advance local economic development and contribute to South Africa’s SDG commitments. Recommendations Policymakers should support sand-based entrepreneurship through funding, training, and regulatory frameworks that promote sustainable resource use. Partnerships between government, academia, and communities are essential to unlocking the full potential of natural resources for inclusive development.